Suppressors of Cytokine Signaling 3 Expression in Eosinophils: Regulation by PGE2 and Th2 Cytokines - Esther López; María Paz Zafra; Beatriz Sastre; Cristina Gámez; Mar Fernández-Nieto; Joaquín Sastre; Carlos Lahoz; Santiago Quirce; Victoria Del Pozo (Clinical and Developmental Immunology)
Asthma and nonasthmatic eosinophilic bronchitis (NAEB) are respiratory disorders characterized by a predominance of Th2 cells and eosinophilic inflammation. Suppressors of cytokine signaling (SOCS) proteins play an important role in Th2-mediated allergic responses through control of the balance between Th1 and Th2 cells, particularly, SOCS3 and SOCS5. The aim of this study was to analyze SOCS expression in human peripheral blood eosinophils from patients with asthma, NAEB and healthy controls. SOCS expression in eosinophils from subjects was demonstrated by different techniques. Results showed that expression of SOCS3 in eosinophils and CD4 T cells from patients was higher than in healthy subjects. In addition, we demonstrated that prostaglandin E2 (PGE2) and Th2 cytokines are able to upregulate SOCS3 production in eosinophils and attenuate its degranulation. In conclusion, eosinophils are able to transcribe and translate SOCS3 protein and can contribute to the regulation of the Th1/Th2 balance through SOCS3 production.